Penguatan Kapasitas Petani Kacang Koro Pedang melalui Pemanfaatan Ekoenzim sebagai Pestisida Alami dan Pupuk Hayati di Desa Angan, Kabupaten Aceh Besar - Hartati Oktarina; Jauharlina Jauharlina; Zaitun Zaitun; Tjut Chamzurni; Yusmanizar Yusmanizar (Universitas Syiah Kuala, 2026)
This community service activity aimed to strengthen the capacity of sword bean farmers in Angan Village, Aceh Besar Regency, through the utilization of eco-enzyme as a natural pesticide and biofertilizer. The main problem faced by farmers was the dependence on synthetic pesticides and fertilizers that potentially harm the environment and human health. The program was conducted in November 2025 through several stages, namely preparation, socialization, implementation, and evaluation. Participants consisted of 20 sword bean farmers and 10 Plant Pest and Disease Control Officers (POPT). The methods included educational sessions on the identification of pests and diseases in legume crops, practical training on producing eco-enzyme from household organic waste, and evaluation using pre-test and post-test assessments. The results showed an increase in participants’ knowledge from 38% before the training to 62% after the training. Participants also gained practical skills in producing eco-enzyme from fruit peels that can be used as a natural pesticide and soil fertilizer. This activity positively contributed to improving farmers’ knowledge and skills in applying environmentally friendly agricultural technologies to support sustainable sword bean cultivation.